Discourse on the State of the Jews Bilingual Edition - Luzzatto, Simone (Studies and Texts in Scepticism, 2019)
Considered the first specimen of a theoretical literature on Jewish political economy, the Discourse is much more. Initially conceived as an apology for the Jewish community of Venice, it is actually replete with sceptical ideas.This volume will essentially aim at refreshing the approach to this work by highlighting and analysing its sceptical background and implications, especially as far as it involves the realm of politics and fashions a sceptical political appraisal of the Jewish people.